The effect of pheniramine on fentanyl-induced cough: a randomized, double blinded, placebo controlled clinical study - Arslan,Zakir (2016)
Abstract Background and objectives: There are many studies conducted on reducing the frequency and severity of fentayl-induced cough during anesthesia induction. We propose that pheniramine maleate, an antihistaminic, may suppress this cough. We aim to observe the effect of pheniramine on fentanyl-induced cough during anesthesia induction. Methods: This is a double-blinded, prospective, three-arm parallel, randomized clinical trial of 120 patients with ASA (American Society of Anesthesiologists) physical status III and IV who aged ≥18 and scheduled for elective open heart surgery during general anesthesia. Patients were randomly assigned to three groups of 40 patients, using computer-generated random numbers: placebo group, pheniramine group, and lidocaine group. Results: Cough incidence differed significantly between groups. In the placebo group, 37.5% of patients had cough, whereas the frequency was significantly decreased in pheniramine group (5%) and lidocaine group (15%) (Fischer exact test, p = 0.0007 and p = 0.0188, respectively). There was no significant change in cough incidence between pheniramine group (5%) and lidocaine group (15%) (Fischer exact test, p = 0.4325). Cough severity did also change between groups. Post Hoc tests with Bonferroni showed that mean cough severity in placebo differed significantly than that of pheniramine group and lidocaine group (p < 0.0001 and p = 0.009, respectively). There was no significant change in cough severity between pheniramine group and lidocaine group (p = 0.856). Conclusion: Intravenous pheniramine is as effective as lidocaine in preventing fentayl-induced cough. Our results emphasize that pheniramine is a convenient drug to decrease this cough.